Private Law Schools In Indonesia: Their Development, Governance And Role In Society - Sinaga, V. Selvie (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Legal education in Indonesia was introduced in the Dutch colonial period. During the early years of Indonesia’s independence, legal education was mostly oﬀered by public universities, and all public law schools were funded entirely by the government of Indonesia. Consequently, the views and policies of these law schools mostly paralleled the government of Indonesia’s policies and views. Later, private institutions participated in providing legal education to Indonesian people interested in studying law. Although private law schools played an important role as an alternative for people who could not enter public law schools for many reasons (e.g., age limit, racial and religious discrimination fears, and political views), they received discriminatory treatment from the government before the 1990s. Prior to the reform era, which began in 1998, the participation of these law schools in the public sector was limited. Only a few alumni from these schools were chosen to hold signifcant positions in the public sector. After 1998, the situation changed, and the role of private law schools has become more signifcant in the country. This paper will document the changes that have been made over time by private law schools in an attempt to attain prominence in Indonesia. Additionally, this paper analyses the role of Indonesian private law schools in society, especially after the reform era started in 1998.